1976
DOI: 10.1159/000231696
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Hydroxyethylstarch Produced in Rabbits by Immunization with a Protein-Hydroxyethylstarch Conjugate

Abstract: Antibodies (ABS) against hydroxyethylstarch (HES) were raised in rabbits by immunization with HES-bovine serum albumin conjugate. ABS against HES were demonstrable by gel diffusion, passive hemagglutination (PH) and passive cutaneous anaphylaxis (PCA); specificity was confirmed by inhibition of PH and neutralization of PCA. No ABS against starch could be induced in comparative experiments. Non-immunogenicity of starch was attributed to its structural similarity with glycogen, widely distributed in animal speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…The a-amylase serum con centrations were determined with the modified [4] phadebas-amylase test (Deutsche Pharmacia, Frankfurt, FRG). The plasma concentrations of both colloids were de termined by the anthrone method [3], HES concentrations were also measured by a single radial immunodiffusion technique, using a recently developed rabbit anti-HES serum [9]. Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The a-amylase serum con centrations were determined with the modified [4] phadebas-amylase test (Deutsche Pharmacia, Frankfurt, FRG). The plasma concentrations of both colloids were de termined by the anthrone method [3], HES concentrations were also measured by a single radial immunodiffusion technique, using a recently developed rabbit anti-HES serum [9]. Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, many of the intracellular vacuoles, especially the larger ones in heavily vacuolated cells of spleen and lymph nodes, appeared empty and revealed only marginal staining. Possible explanations for this phenomenon could be the washout of the highly water-soluble HES during the pro cesses of fixation, embedding and immunohistochemistry, but also lysosomal reduction of HES to undetectable metabolites [28,29], Earlier experiments showed that the antigenic determinant of HES, detected by the poly clonal rabbit anti-HES antiserum, consisted most probably of short sequences of hydroxyethylatcd glucose units [22], Therefore, our immunohistochemical results do not make possible any distinction between stor age of complete HES molecules with molecu lar weight 200.000 daltons or HES degrada tion products in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of specific antibodies against gelatine preparations was possible in rabbits and guinea pigs [19], However, a correlation between the occurrence of the gelatine-reac tive antibodies and anaphylactoid reaction was not shown, even in patients with de creased antigelatine antibody titres after gela tine infusion [20][21][22], Amylopectin -the main component of corn starch -is the basic substance for the synthesis of HES. Due to its structural simi larity with glycogen -an ubiquitous com pound in warm blooded organisms -immunogenicity of starch is expected to be unlikely [23][24][25]. Nevertheless, in theory, substitution of amylopectin molecules with hydroxyethyl groups might increase its immunogenic and antigenic potential [24], Earlier investigations with different modes of HES application (infusion or repeated i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in theory, substitution of amylopectin molecules with hydroxyethyl groups might increase its immunogenic and antigenic potential [24], Earlier investigations with different modes of HES application (infusion or repeated i.m. administration of mg dosage) failed to induce immunization and formation of precipitating antibodies in man [24,26,27], In 8 patients with adverse reactions after HES infusion no precipitating antibodies could be detected by double immunodiffusion, a test with rela tively low sensitivity [25,28], There is only one study describing the exis tence of preformed HES-reactive antibodies in man. Normal subjects, who had never had any previous contact with HES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation